Women's Silent resistance Against Hegemony In The Scarlet Letter, Bekisar Merah, and Belantik: a comparative analysis - R.B. Edi Pramono (UPP FIB UGM (No.02;Juni 2013;Vol.25), 2013)
Women's Silent resistance Against Hegemony In The Scarlet Letter, Bekisar Merah, and Belantik: a comparative analysis: Hegemoni, penindasan, perlawanan diam, pranata patriakal